Genetic patterns of Streptococcus uberis isolated from bovine mastitis - Elina B Reinoso; Mirta C Lasagno; Liliana M Odierno (Revista Argentina de Microbiología, 2015)
The aim of this study was to evaluate the genotypic relationships among 40 Streptococcus uberis isolated from bovine mastitis by using pulsed-field gel electrophoresis (PFGE). Additionally, the association between PFGE patterns and virulence profiles was investigated. The isolates exhibited 17 PFGE patterns. Different strains were found within and among herds; however, a low number of isolates within the same herd shared an identical PFGE type. No association between PFGE patterns and virulence profiles was found. However, the detection of specific strains in some herds could indicate that some strains are more virulent than others. Further research needs to be undertaken to elucidate new virulence-associated genes that might contribute to the capability of these strains to produce infection.